Implementation of the Independent Curriculum in the Pancasila Student Profile Dimension of Class 2A Students at SDN 2 Jenggala for the 2023/2024 Academic Year - Jihani, Gusnia; Arzani, M.; Eliyana (Lembaga Bale Literasi, 2024)
Abstract Gusnia Jihani (2024), this research aims to describe the implementation of the independent curriculum in the dimensions of the Pancasila student profile for class 2A students at the Jenggala 2 Elementary School, Tanjung sub-district. This research was carried out at the Jenggala 2 Elementary School, Tanjung sub-district on class 2A students in the second semester of the 2023/2024 academic year with a total of 23 students. This type of research is descriptive qualitative research, the data collection techniques used in this research are observation, interviews and documentation. The information collected came from the principal, class 2A teachers and P5 teachers, as well as class 2A students at Jenggala 2 Elementary School. The data analysis technique used in this research goes through several stages including 1) limiting the research study. 2) develop questions. 3) planning the stages of data collection and paying attention to the results of previous observations. 4) check the collected data again. 5) Systematically organize notes from observations and interviews. 6) describe and elaborate on all data, namely observations and interviews. The results of this research in implementing the independent curriculum discuss 3 important points, namely: 1) in the learning planning for class 2A students the teacher has created teaching modules that are appropriate to learning at Jenggala 2 State Elementary School, 2) in its implementation or implementation the teacher always provides routine habits to the participants students and provide examples of good behavior in implementing the mutual cooperation dimension in class 2A, and 3) the positive impact found in implementing the pancasila student profile, namely that students become accustomed to doing positive things such as dressing neatly, praying before and after teaching. Keyword : Implementation of the Independent Curriculum, Pancasila Student Profile, and Mutual Cooperation Dimensions.